2019
DOI: 10.1002/ps.5526
|View full text |Cite
|
Sign up to set email alerts
|

BABA application improves soybean resistance to aphid through activation of phenylpropanoid metabolism and callose deposition

Abstract: BACKGROUND Beta‐aminobutyric acid (BABA) confer plant resistance to a broad spectrum of biotic and abiotic stresses. The soybean aphid (SBA), is native to eastern Asia and is a predominant insect pest of soybean. Both isoflavone and lignin pathway are important branches of the general phenylpropanoid pathway, which would be likely associated with resistance against soybean aphid. However, little is known about the role of the phenylpropanoid pathway in defense response to SBA as induced by BABA application. RE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 74 publications
(153 reference statements)
0
16
0
Order By: Relevance
“…Furthermore, BABA priming affects the methylome of plants, resulting in a transcriptional memory of the event which can affect following generations (Kuźnicki et al, ). Recent studies showed how BABA perception reshapes the primary metabolism of plant cells by boosting the TCA cycle and mobilizing starch reservoirs towards callose synthesis and deposition at the infection sites (Gamir et al, ; Pastor, Balmer, Gamir, Flors, & Mauch‐Mani, ; Yao, Zhong, Wang, Yan, & Wu, ).…”
Section: Interconnections Between Gaba and Other Stress‐related Aminomentioning
confidence: 99%
“…Furthermore, BABA priming affects the methylome of plants, resulting in a transcriptional memory of the event which can affect following generations (Kuźnicki et al, ). Recent studies showed how BABA perception reshapes the primary metabolism of plant cells by boosting the TCA cycle and mobilizing starch reservoirs towards callose synthesis and deposition at the infection sites (Gamir et al, ; Pastor, Balmer, Gamir, Flors, & Mauch‐Mani, ; Yao, Zhong, Wang, Yan, & Wu, ).…”
Section: Interconnections Between Gaba and Other Stress‐related Aminomentioning
confidence: 99%
“…β-aminobutyric acid (BABA), a non-protein amino acid, has been reported as a link between heat tolerance, biotic stress, and ABA signaling. Plants treated with BABA become resistant to abiotic as well as biotic stress [155][156][157][158]. The ibs3, a BABA-induced sterility mutant, exhibits defected regulation of ABA1, salt resistance, and BABA-induced pathogen [159].…”
Section: Biotic Stress Signaling Integration With the Aba Signaling Pmentioning
confidence: 99%
“…Furthermore, ABA positively regulates starch amylase (BAM1) and suppresses beta-1,3glucanase (PR2), leading to augmented callose deposition to defend against pathogen infection (Oide et al, 2013;Gamir et al, 2018). Likewise, callose accumulation is effective for plant resistance to phloem-sucking insects (Cheng et al, 2013;Liu et al, 2017;Yao et al, 2019). When attacked by brown planthoppers (Nilaparvata lugens Stål), callose deposition is activated around sieve plates in rice (Oryza sativa), which is a disadvantage for the fitness of brown planthoppers (Hao et al, 2008).…”
Section: Introductionmentioning
confidence: 99%